Direct fluorination of K2B12H12 and synthesis and characterization of metal salts of B12F122- - Peryshkov, Dmitry V., author; Strauss, Steven H., advisor; Rappe, Anthony K., committee member; Elliott, C. Michael, committee member; Bernstein, Elliot R., committee member; Ridley, John R., committee member (Colorado State University. Libraries, 2011)
A significantly improved large-scale (10 g) perfluorination of K2B12H12 is described. The advantages of the new procedure are: (i) a ten-fold increase in the scale of the reaction with no sacrifice in yield or product purity; (ii) acetonitrile is used as the solvent instead of anhydrous HF; and (iii) a glass reaction vessel is used instead of a Monel reactor. DFT calculations and experimental data are reported that suggest that the absence of acidity significantly increased the rate and improved the efficiency of the reaction. Number of salts of Li+; Na+; K+; Rb+; Cs+; NH4+, Ag+; Mg2+; Ca2+; Ba2+; Co2+; Ni2+; and Zn2+ and the B12F122- anion were prepared and 24 crystal structures (some compounds were prepared by others) were determined. The thermal stabilities of the Mm(L)nB12F12 salts were studied by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). It was found that Cs2B12F12 is stable up to 600 °C under an inert atmosphere, which is the highest temperature among weakly coordinating fluoroanions. The compounds K2B12F12, Rb2B12F12, Cs2B12F12, and Ag2B12F12 were prepared as ligand-free solids. It was found that the K2(H2O)0,2,4B12F12 system of compounds can undergo rapid interconversion among the three crystalline phases, two of them reversibly in presence of water vapor. The reversible interconversion was found to be a reconstructive (i.e., topotactic) solid-state reaction and, when carried out very slowly, a single-crystal-to-single-crystal transformation. The exchange of H2O(g) with either D2O or H218O in crystalline K2(D2O)2B12F12 or K2(H218O)2B12F12 at 25 °C was also rapid. The new concept of latent porosity, as ligands rapidly enter a lattice and displace some of the weak and non-directional M•••F(B) bonds in salts of the large, highly-symmetric, superweak anion B12F122-, is presented and discussed.